A influência do metabolismo no cálculo do PMV da norma ISO 7730 (2005) - Avelino, Alinny Dantas (2019)
Thermal comfort is influenced by six factors and the accuracy of each will influence the overall accuracy of the PMV. One of the possible factors for inequalities is the determination of the metabolism rate. Thus, this research analyses whether the PMV calculated as a function of the metabolism obtained through the analysis of the personal variables of students in air-conditioned smart teaching environments is more similar to the thermal sensation vote than the model presented by ISO 7730 (2005). The personal variables were obtained through a structured questionnaire while the health and thermal variables were measured. The sample was 210 people in 7 settings totaling a sample of 517 data. In order to obtain a value for the metabolism, the bisection method was used. Generalized linear models were developed using methods and functions related to the g function, which relates the calculated metabolism to the evaluated variables. Generalized linear models were generated in order to improve the accuracy of the subjects' metabolism. A difference was observed between the PMV and the TSV of the subjects. In the situations of this research, the PMV overestimated and underestimated the opinion of the subjects. Although a lot of students have higherthan-expected metabolic rates, the central trend is only 0.6 met from what was recorded by the standard. Regarding the generation of the models, in every group that the variable weight was analyzed, it was considered in the model. The same occurred for the variables final heart rate and dry eyes sensation. Not drinking alcohol reduces metabolism by 0.16528 met. The weight variable shows little influence when altered. The variation of this variable decreases the metabolism by up to 0.67578 met as the pressure increases. An increase in heart rate at rest causes a decrease in metabolism while an increase in final heart rate causes an increase in heart rate. The PMV that best fit the opinion of the subjects evaluated in this research was the PMV calculated through the metabolism model created in this research. The study is limited to the environment, activity and set of subjects that fit the group initially proposed.